Factors Associated with Help-Seeking in Obsessive-Compulsive Disorder Patients - ขำแก้ว, อัญชิดา; สายพานิชย์, รัตนา; วิสาจันทร์, ภัทรพร; จุลเกตุ, สุดาวรรณ (Journal of the Psychiatric Association of Thailand, 2019)
Objectives : To study about the factors associated with treatment-seeking among the obsessive-compulsive disorder (OCD) patients Methods : A cross-sectional descriptive study was conducted in 87 OCD patients aged 18-80 years in the outpatient clinic, Department of Psychiatry, Ramathibodi Hospital from July 2017-June 2018. Participants were divided into 2 groups, which were early treatment-seeking and delayed treatmentseeking group. The questionnaire consisted of demographic characteristics, Thai self-report version of the Yale-Brown Obsessive-Compulsive Scale-Second Edition, Interview on help-seeking (Thai version). Data were analyzed using descriptive statistics and chi-square test. Results : Total of 87 patients, 62.1% were the delayed treatment-seeking group and 37.9% were the early treatment-seeking group. In the delayed group, the mean length of delay in seeking treatment was 9.52±7.483 years. There were no difference in socioeconomic status, comorbidity and severity of the disorder between both groups, but the patients with less income 30,000/month were likely to be delayed their treatment-seeking (P =0.023). Both groups recognized the problem when they realized that their behaviors changed, they couldn’t control their behavior/thoughts and symptoms interfered more in their daily activities. Regards to factors which delayed the treatment-seeking, both groups mostly reported the belief that the problem was not serious, thoughts that they could control the problem and the belief that problem was temporary. Factors that affected the treatment-seeking were the problem became more and more disturbing, the problem was not extinguished and couldnot be controlled, and the problem interfered daily activities. Moreover, the early treatment-seeking group had higher income, reported more belief that the problem was temporary and more fear about what would be happening to them than the other group. Conclusion : Factors influencing the decision-making of patients were the realization that their behaviors have changed, the symptoms were uncontrollable and disruptive to life. Factors that delayed treatment were thinking about a problem that it was not serious, controllable and temporary. Therefore, raising awareness of the problem and improving knowledge about the obsessive-compulsive disorder will help patients to access the treatment more quickly, have better outcomes and quality of life.